2006
DOI: 10.1016/j.yqres.2005.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for high-frequency late Glacial to mid-Holocene (16,800 to 5500 cal yr B.P.) climate variability from oxygen isotope values of Lough Inchiquin, Ireland

Abstract: A 7.6-m core recovered from Lough Inchiquin, western Ireland provides evidence for rapid and long-term climate change from the Late Glacial period to the Mid-Holocene. We determined percentage of carbonate, total organic matter, mineralogy, and δ18Ocalcite values to provide the first high-resolution record of climate variability for this period in Ireland. Following deglaciation, rapid climate amelioration preceded large increases in GISP2 δ18Oice values by ∼2300 yr. The Oldest Dryas (15,100 to 14,500 cal yr B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 44 publications
2
62
0
1
Order By: Relevance
“…The absolute value of authigenic carbonates precipitated during this interval shows a spatial variation which is consistent with known variations in the δ 18 O value of modern day precipitation, i.e. the early Holocene peak in δ 18 O values is higher in western sites such as Loch Inchquin and Haweswater, ca -4.0 to -4.5‰ (Marshall et al, 2002;Diefendorf et al, 2006;2008)) than at eastern sites such as Lundin Tower and Palaeolake Flixton, ca -6‰ (Whittington et al, 1996). However, at all sites the magnitude of the decrease is relatively consistent, between 2 and 3‰.…”
Section: An Early Holocene Oxygen Isotope Depletion Trend In British supporting
confidence: 82%
See 1 more Smart Citation
“…The absolute value of authigenic carbonates precipitated during this interval shows a spatial variation which is consistent with known variations in the δ 18 O value of modern day precipitation, i.e. the early Holocene peak in δ 18 O values is higher in western sites such as Loch Inchquin and Haweswater, ca -4.0 to -4.5‰ (Marshall et al, 2002;Diefendorf et al, 2006;2008)) than at eastern sites such as Lundin Tower and Palaeolake Flixton, ca -6‰ (Whittington et al, 1996). However, at all sites the magnitude of the decrease is relatively consistent, between 2 and 3‰.…”
Section: An Early Holocene Oxygen Isotope Depletion Trend In British supporting
confidence: 82%
“…A review of the literature indicates that the pattern of δ 18 O values seen at Flixton, is also seen at Loch Inchquin (west coast of Ireland (Diefendorf et al, 2006;2008)), Haweswater (the English Lake District (Marshall et al, 2002;2007)), Lundin Tower (southeast Scotland (Whittington et al, 1996)) and Lake Tibetanus (northern Sweden ((Hammarlund et al, 2002) (Figure 7). It should be highlighted that the chronology of many of these sites is of low resolution, there is, therefore, no implication that the timing of these peaks are synchronous or that the onset of the depletion trend is uniform across the British Isles.…”
Section: An Early Holocene Oxygen Isotope Depletion Trend In British mentioning
confidence: 95%
“…Authigenic carbonates from lake sediment cores retrieved from Lough Gur (southwestern Ireland) by Ahlberg et al This is broadly in line with the decrease in  18 O spel inferred from the spatial correlations for the western end of the speleothem transect presented here (Figure 6b). Similarly, in a study of late Glacial to Holocene lake carbonates from Lough Inchiquin (western Ireland), Diefendorf et al (2006) demonstrated that  18 O values in authigenic calcites increased rapidly at c. 10.5 ka, interpreted to reflect the onset of Boreal warming in western Ireland in the early Holocene.…”
mentioning
confidence: 90%
“…The millennial-to century-scale climatic events, such as the last glacial maximum (LGM), the Meiendorf (MD), Bølling (BO) and Allerød (AL) warming phases, the Oldest Dryas (OstD), Older Dryas (OD) and Younger Dryas (YD) cold events were exposed by highresolution and accurately dated proxy records from terrestrial archives (Wang et al, 2001;Yuan et al, 2004;Svensson et al, 2008) and lake sediments (Litt and Stebich, 1999;Yu and Eicher, 2001;Nakagawa et al, 2005;Diefendorf et al, 2006;Stebich et al, 2009;Zhao et al, 2013), providing important information about the rate, amplitude and driving mechanisms of these climatic events.…”
Section: Introductionmentioning
confidence: 99%